A Diene‐Containing Noncanonical Amino Acid Enables Dual Functionality in Proteins: Rapid Diels–Alder Reaction with Maleimide or Proximity‐Based Dimerization. Issue 25 (14th May 2019) - St. Amant, Andre H.; Huang, Fengying; Lin, Jia; Rickert, Keith; Oganesyan, Vaheh; Lemen, Daniel; Mao, Shenlan; Harper, Jay; Marelli, Marcello; Wu, Herren; Gao, Changshou; Read de Alaniz, Javier; et al.
Abstract: Here, we describe a diene‐containing noncanonical amino acid (ncAA) capable of undergoing fast and selective normal electron‐demand Diels–Alder (DA) reactions following its incorporation into antibodies. A cyclopentadiene derivative of lysine (CpHK) served as the reactive handle for DA transformations and the substrate for genetic incorporation. CpHK incorporated into antibodies with high efficiency and was available for maleimide conjugation or self‐reaction depending on position in the amino acid sequence. CpHK at position K274 reacted with the maleimide drug‐linker AZ1508 at a rate of ≈79 m −1  s −1 to produce functional antibody–drug conjugates (ADCs) in a one‐step process. Incorporation of CpHK at position S239 resulted in dimerization, which covalently linked antibody heavy chains together. The diene ncAA described here is capable of producing therapeutic protein conjugates with clinically validated and widely available maleimide compounds, while also enabling proximity‐based stapling through a DA dimerization reaction. Abstract : A diene‐containing noncanonical amino acid (ncAA) undergoes selective normal electron‐demand Diels–Alder (DA) reactions following its incorporation into antibodies. A cyclopentadiene derivative of lysine (CpHK) served as the reactive handle for DA transformations and the substrate for genetic incorporation. CpHK incorporated into antibodies with high efficiency and was available for maleimide conjugation or self‐reaction depending on position in the amino acid sequence.